1997
DOI: 10.1046/j.1365-3059.1997.d01-54.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between stem canker, stolon canker, black scurf (Rhizoctonia solani) and yield of potato (Solanum tuberosum) under different agronomic conditions

Abstract: Relationships between diseases caused by Rhizoctonia solani on different parts of potato plants (Solanum tuberosum) at different stages of crop growth were investigated under selected agronomic conditions. The effects of different densities of tuber-borne inoculum, date of planting, irrigation, size of seed tubers and their interactions on the incidence of stem and stolon canker during crop growth, the incidence and severity of black scurf and the yield of progeny tubers at harvest were quantified in a multifa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Our results indicate that seed inoculum levels of 12% of the tuber surface covered with black scurf are enough to consistently increase disease incidence and severity. Simons and Gilligan (1997) also found a similar relationship between seed inoculum level and the incidence of stem canker. In contrast, other authors have reported no influence of seed tuber inoculum levels of less than 15% to (Gudmestad et al 1979, James andMcKenzie 1972).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our results indicate that seed inoculum levels of 12% of the tuber surface covered with black scurf are enough to consistently increase disease incidence and severity. Simons and Gilligan (1997) also found a similar relationship between seed inoculum level and the incidence of stem canker. In contrast, other authors have reported no influence of seed tuber inoculum levels of less than 15% to (Gudmestad et al 1979, James andMcKenzie 1972).…”
Section: Discussionsupporting
confidence: 61%
“…As stolons are pruned and tuber set is reduced, there are fewer tubers per plant to act as sinks for products of photosynthesis. This can lead to uneven tuber growth, thereby increasing yields of off-grade tubers (Simons and Gilligan 1997). The fungus may also form brown to black sclerotia on the surfaces of mature tubers, a symptom that is commonly referred to as black scurf.…”
mentioning
confidence: 99%
“…This disrupts the movement of water and nutrients throughout the plant and eventually stems may be pruned (Back et al 2006). The collective name for these symptoms is widely known as stem canker (Read et al 1989;Simons and Gilligan 1997). In a similar manner, stolons and roots can also be infested and pruned by R. solani and the resulting symptoms are known as stolon and root canker, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Most reports claim that Rhizoctonia disease of potato does not usually reduce total tuber yield (e.g. Simons and Gilligan 1997). It may however substantially degrade tuber quality and marketability, which is the consequence of one or more of the following: (a) hard sclerotia on tuber surfaces (black scurf), (b) greater numbers of non-target size tubers, (c) tuber greening, (d) sessile tubers or 'little potato' and (e) malformed tubers (Scholte 1989;Simons and Gilligan 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Rhizoctonia solani (AG3) is a soil-borne fungal pathogen that is widespread in potato (Solanum tuberosum L.) growing land in the UK (Wale et al, 2004;Woodhall et al, 2007), causing stem and stolon canker and black scurf at different growth stages of the plant (Hide et al, 1973;Scholte, 1989;Simons & Gilligan, 1997;Wale et al, 2008;Woodhall et al, 2008). Black scurf on tubers during plant senescence reduces tuber quality and causes marketable yield losses approaching 30% (Banville, 1989).…”
mentioning
confidence: 99%